Symbol and Substance in Local Government Workforce Development: First Source Hiring Programs. (2nd October 2017) - Atkinson, Christopher L.
Abstract : First Source programs intend to spur interviewing/hiring of hard-to-hire or disadvantaged individuals on local government contracts. Such programs are belief-based, rooted in values that must be translated into outcomes and subjected to diligent evaluation processes. The failure of values-based programs to achieve desired outcomes is an ethical consideration. This article views two First Source programs (in Washington, DC, and Providence, RI) through the lens of semiotics, asking what the program language says about symbol and meaning in public policy, and what these programs have led to in outcomes for workforce development. The programs show potential for community benefit, but ambiguity in detailing expectations and program processes may lead to underwhelming results, even though the passage or existence of the program might satisfy advocacy groups.